A study of "up" - "down" in english and "lên" - "xuống" in vietnamese: a cognitive semantics perspective (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study aimed to discover the syntactic, semantic in the light of cognitive semantics of “up” –“down” in English and “lên” –“xuống” in Vietnamese. The study was carried out through the adoption of qualitative, contrastive approaches to examine syntactic and semantic devices signaling the conceptual meaning of “up” –“down” in English and “lên” –“xuống” in Vietnamese. I would like to collect sentences, phrases containing instances of “up” – “down” and” and “lên” – “xuống” in both languages from books, novels, short stories, dictionaries with 300 English samples and 300 Vietnamese ones as the population of the observed instances. The most important and significant aspect of the study, the similarities and differences between English and Vietnamese ways of orienting “up” –“down” in English and “lên” –“xuống” in Vietnamese in the light of cognitive semantics, was presented in order to help learners, teachers and translators have better use of these orentational prepositions. In view of cognitive semantics, not only do “up” – “down” denote quantity senses and “lên” – “xuống” denote senses of status but they also denote a number of other senses. This thesis also provided some suitable methods to coding the meaning of “up” –“down” in English and “lên” –“xuống” in Vietnamese.